Semantic digital library for 4 mazhab in fiqh - Mohamad Hafizuddin bin Mohamed Najid (Kulliyyah of Information Communication & Technology, International Islamic University Malaysia, 2014)
Semantic Digital Libraries give users a better understanding of the collections. This research is aimed at developing ontology for use in a Semantic Digital Library. The research objectives are to identify the subjects and sources for the ontology development to construct the semantic relationship predicates and to verify the semantic relationship between the 4 Mazhab in Fiqh. This research applies ontology development and semi-structured face-to-face interview with the Head of Programme Degree in Information Management and Sunnah Studies from Islamic Science University of Malaysia (USIM). The seven semantic relationship predicates selected and used in this research are 'quotes', 'is related to', 'has similar content', 'defines', 'explains', 'has subject' and 'is part of'. The challenges faced in this research are related to the semantic relationship construction. The seven predicates fit well into the Semantic Digital Library.